EVALUASI PELAKSANAAN PROGRAM MICRO TEACHING PADA MAHASISWA PROGRAM STUDI PENDIDIKAN MATEMATIKA FKIP UNIVERSITAS GRAHA NUSANTARA - Harahap, Adek Nilasari; Ambyar, Ambyar; Aziz, Ishak (Institut Pendidikan Tapanuli Selatan, 2023)
This study aims to determine the effectiveness of the implementation of the micro teaching program for the 2021–2022 academic year for students of the Mathematics Education Study Program, Faculty of Teaching and Education, Garaha Nusantara University. Descriptive research was conducted using a survey study research design. This study used 30 students as the sample. Based on data analysis, 62.92% of students who answered a questionnaire about the level of preparation for micro teaching activities were categorized as having done so. This conclusion is further supported by survey data on aspects of the supervisor's responsibilities in the implementation of micro teaching, in particular the 43.33% classification of which is classified as moderate/sufficient in terms of student guidance. Based on the survey results, it was found that 50.84% of students were quite capable of carrying out micro teaching practices in the microteaching laboratory. Based on the percentage of data, it is stated that in terms of the implementation of micro teaching, it has not achieved success because it has not achieved a 100% score from all aspects of the assessment which strongly supports the implementation of micro teaching practices.